Tax Policy and Financial Access: Implications for Entrepreneurial Intention and Entrepreneurial Behavior Among Generation Z - Priandhita Sukowidyanti Asmoro; Edlyn Khurotul Aini; Ferina Nurlaily (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study develops a framework based on the Theory of Planned Behavior and focuses on perceived behavioral control. The Theory of Planned Behavior is extended in this research by proposing that tax policy and financial access are predictors of Generation Z's entrepreneurial intention and behavior. Based on the researcher's knowledge, tax policy and financial access have never been studied concurrently for their impact on entrepreneurial behavior in Indonesia. The model was tested empirically on 500 entrepreneurial students from four public universities in Indonesia. Questionnaire surveys were administered to respondents identified using the random purposive sampling technique. Primary data were processed according to path analysis procedures using SPSS 25. The Theory of Planned Behavior is supported by the seven hypotheses stated in this study. Tax policies and financial access directly affect entrepreneurial intentions and entrepreneurial behavior. Entrepreneurial intentions can also mediate the impact of tax policy and financial access on entrepreneurial behavior.